Monitoring and verification in the biological-weapons area. Issue 4 (1st September 2020) - Kraatz-Wadsack, Gabriele
ABSTRACT: This article provides a brief overview of the ongoing monitoring and verification (OMV) regime in Iraq in the biological-weapons area. As an integral part of the formal ceasefire arrangement in 1991, the United Nations Security Council established an international verification regime encompassing nuclear, biological, and chemical weapons and some ballistic missiles. The verification regime was built on two mutually supportive pillars. One pillar related to disarmament validation, i.e., verifying that all prohibited weapons, facilities, and related items and certain ballistic missiles in Iraq were destroyed or rendered harmless, and all past weapons-of-mass-destruction (WMD) activities had ceased. The second pillar was ongoing monitoring to continuously verify that non-proscribed activities were not being diverted to reconstitute WMD programs. Biological-weapons disarmament and OMV in Iraq provide an example of an effective system that may serve as a reference point for future efforts.